2010
DOI: 10.1124/dmd.110.033670
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Vabicaserin in Mice, Rats, Dogs, Monkeys, and Humans

Abstract: ABSTRACT:Vabicaserin is a potent 5-hydroxytryptamine 2C agonist that is currently being developed for the treatment of the psychotic symptoms of schizophrenia. In this study, in vitro and in vivo metabolism of vabicaserin was evaluated in mice, rats, dogs, monkeys, and humans, and the structures of the metabolites were characterized by liquid chromatography/mass spectrometry and NMR spectroscopy. Vabicaserin underwent three major metabolic pathways in vitro: NADPH-dependent hydroxylation, NADPH-independent imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…M12 accounted for greater than 50% of total drug-related material in circulation based on mass spectrometry and UV response data. Based on the mixed matrix method (Tong et al, 2010a;Ma and Chowdhury, 2011;Takahashi et al, 2017), M12 was disproportionate in human circulation and not covered in rat and dog toxicology species (less than 0.1% preclinical/clinical exposure) and this was subsequently confirmed by a bioanalytical assay with an authentic standard. M12 was determined to be formed and circulating in rabbit plasma and provided coverage for the embryo fetal development study (seg II).…”
Section: Case Study 5: Ribociclibmentioning
confidence: 97%
See 3 more Smart Citations
“…M12 accounted for greater than 50% of total drug-related material in circulation based on mass spectrometry and UV response data. Based on the mixed matrix method (Tong et al, 2010a;Ma and Chowdhury, 2011;Takahashi et al, 2017), M12 was disproportionate in human circulation and not covered in rat and dog toxicology species (less than 0.1% preclinical/clinical exposure) and this was subsequently confirmed by a bioanalytical assay with an authentic standard. M12 was determined to be formed and circulating in rabbit plasma and provided coverage for the embryo fetal development study (seg II).…”
Section: Case Study 5: Ribociclibmentioning
confidence: 97%
“…It is extensively metabolized in animal species (mouse, rat, dog, monkey) and in human both in vitro and in vivo (Tong et al, 2010b). The predominant metabolic pathway in humans was due to carbamoyl glucuronidation; however, other metabolic pathways including oxidation (with formation of multiple hydroxyl metabolites) and formation of imine and nitrone metabolites were also observed (Tong et al, 2010a was also the major entity in human urine, and this metabolic pathway may account for >50% of the total clearance based on urinary concentrations (Tong et al, 2010b). Even though formation of M6 was observed in animal species, the systemic exposures to M6 relative to parent appeared to be less than humans (higher amounts in mice, dogs and monkeys; very low amounts in rats and rabbits), as determined using validated LC/MS/MS methods.…”
Section: Case Study 2: Vabicaserinmentioning
confidence: 99%
See 2 more Smart Citations
“…In a compound series recently developed at Wyeth Research, vabicaserin (SCA-136) was identified as a selective 5-HT 2C R full agonist (K i = 3 nM; efficacy 100% relative to 5-HT), a 5-HT 2B R antagonist (IC 50 = 29 nM) and a very weak 5-HT 2A R antagonist (IC 50 = 1,650 nM) (Rosenzweig-Lipson, et al, 2007a; Tong, et al, 2010a; Tong, et al, 2010b). Vabicaserin has been in clinical trials to evaluate antipsychotic potential (www.clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%